Response of native maize from Mexican highlands to ear rot, under natural infection. - Briones-Reyes, Dolores; Castillo-González, Fernando; Chávez-Servia, José Luis; Aguilar-Rincón, Víctor Héber; García-de Alba, Carlos de León; Ramírez Hernández, Antonio (Agronomía Mesoamericana, 2015)
The objective of this study was to evaluate the response to natural infection of Fusarium spp. on 55 native maize populations. The populations evaluated were collected in five states of Mexico, and planted in three locations in 2010 and 2011 under rainfed conditions. The average percentage of ear rot was significantly different among maize populations, locations and among populations within locations and years. The population groups of kernel color showed differences among them, where yellow and red groups presented the lower infection percentages. In the relation to geographic provenance, maize populations of Oaxaca presented less damage than those from Mexico, Puebla, Tlaxcala and Guerrero states. In grain yield, there were differences among locations, populations and years. In the significant interaction between population groups and locations showed that populations with local origin presented low ear rot percentage and major yield, which suggest a coevolution and coadaptation process. The higher ear weight was obtained in 2011, where the Oaxaca populations were outstanding. It is possible to infer that native maize populations from Oaxaca are a potential source of resistance or tolerance to ear rot caused by Fusarium spp.